Law on Residence - The National Assembly (2006)
This Law provides for citizens' right to freedom of residence in the territory of the Socialist Republic of Vietnam; the residence registration and administration order and procedures; the rights and esponsibilities of citizens, households, agencies and organizations regarding residence registration and administration. Residence means a citizen's living at a place in a commune, ward or township in the form of permanent residence or temporary residence.